Organizatsiia kompleksnoi sistemy vospitatel'noi raboty v vuze - Balabanova V. A. (Pedagogical Technology in the Edauctional System: Innovations and Possibilities, 2021)
Educational work is a priority in education. This article examines the features of the organization of a planned system of educational work in modern conditions, outlines general approaches to the organization of the system of educating young people in a university
Keywords: воспитание; студенты; внеучебная деятельность; students; система воспитательной работы; extracurricular activities; upbringing; educational work system